2016
DOI: 10.3892/mmr.2016.4813
|View full text |Cite
|
Sign up to set email alerts
|

Icariin inhibits oxidized low-density lipoprotein-induced proliferation of vascular smooth muscle cells by suppressing activation of extracellular signal-regulated kinase 1/2 and expression of proliferating cell nuclear antigen

Abstract: Icariin, a flavonoid isolated from the traditional Chinese herbal medicine Epimedium brevicornum Maxim, has been shown to possess anti-inflammatory, anti‑oxidant and anti-atherosclerotic activities in vivo and in vitro. The aim of the present study was to investigate the effects of icariin on oxidized low‑density lipoprotein (ox-LDL)-induced proliferation of vascular smooth muscle cells (VSMCs) and the possible underlying mechanism. VSMCs were cultured and pre‑treated with various concentrations of icariin (0,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…A prior study found that ICA treatment evidently ameliorated angiotensin II (AngII)-induced cell proliferation in human brain vascular SMCs (HB-VSMCs) (Dong et al, 2019). Meanwhile, our colleagues demonstrated that oxidized low density lipoprotein (ox-LDL) significantly increases cell viability of HA-VSMCs, yet ICA suppressed ox-LDL-induced HA-VSMC proliferation in a concentration-dependent manner (Hu et al, 2016). Previous studies have clearly demonstrated that ox-LDL can promote cell proliferation via activating PDGF receptor-β (PDGFR-β) pathway (Vindis et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A prior study found that ICA treatment evidently ameliorated angiotensin II (AngII)-induced cell proliferation in human brain vascular SMCs (HB-VSMCs) (Dong et al, 2019). Meanwhile, our colleagues demonstrated that oxidized low density lipoprotein (ox-LDL) significantly increases cell viability of HA-VSMCs, yet ICA suppressed ox-LDL-induced HA-VSMC proliferation in a concentration-dependent manner (Hu et al, 2016). Previous studies have clearly demonstrated that ox-LDL can promote cell proliferation via activating PDGF receptor-β (PDGFR-β) pathway (Vindis et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…Recently, emerging studies have reported ICA regulates cell cycle progression and proliferation in various cell types. ICA exerted suppressive effects on medulloblastoma cells (Sun et al, 2016b), osteosarcoma cells (Ren, Zhu & Liu, 2018) and human aortic smooth muscle cells (HA-VSMCs) (Hu et al, 2016). Further, the induction of G0/G1 phase arrest was observed in cardiomyocyte and breast cancer cells after treatment with ICA (Zhu et al, 2005;Cheng et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Icariin has been shown to significantly prohibit the proliferation of vascular smooth muscle cells (VSMCs) and the activation of ERK1/2. Moreover, icariin also induced G1/S phase cell cycle arrest and decreased the expression of PCNA in VSMCs [ 89 ]. Based on these results, it was proposed that the inhibitory effect of icariin on the proliferation of VSMCs might be responsible for the suppression of tumor metastasis.…”
Section: Molecular Mechanisms Of Anticancer Activity Of Icariin Anmentioning
confidence: 99%
“…5,6 Moreover, the anti-angiogenic activity of ICA was confirmed by the inhibition of the proliferation of vascular smooth muscle cells through inactivation of the ERK1/2 signaling pathway. 7 However, we are not aware of any studies focused on the anti-adhesion roles and mechanisms of ICA in blocking epidural adhesion formation.…”
Section: Introductionmentioning
confidence: 99%